(3GdSjGSI GdSYQjI aj EWGQ GdYhdeI GdGbJUGOjI (B:s (3MGdI GdLRGFQ (B/s - (3NHGHI, YHO Gddgs ((3GdGScfOQjI(B: s (3eDSSI GdKbGaI GdLGeYjI(B, s, 2009)
(3GdSYQ aj GdfXQjI GdGbJUGOjI, echfGJ GdSYQ, GdfXGe GdGbJUGOj GdeNJdW h GdfXGe GdGbJUGOj GdQCSeGdj h GdfXGe GdGbJUGOj GdGSdGej, JCKjQ GdYhdeI Ydi GdSjGSI GdSYQjI, eGgjI GdYhdeI, GdYhdeI GdGbJUGOjI h BKGQgG, GdSjGSI GdSYQjI aj GdLRGFQ h BaGbgG aj Xd GdYhdeI, SjGSI GdCSYGQ aj GdLRGFQ, EUdGM GdSjGSI GdSYQjI h GdGSJQGJjLjI GdSYQjI h BaGbgG GdeSJbHdjIs
(3HHdjhZQGajG(B: (3U(B.606s
Keywords: (3GdLRGFQ(B- (3GdSjGSI GdfbOjIs; (3GdSYQs; (3GdSjGSI GdfbOjIs; (3GdYhdeIs